Tip Hypospadias Repair: A Retrospective Review of The Factors Associated with Positive Surgical Outcomes - Dhangar, Sanjay P; Iqbal, Shams; K Plash, Sonu; Patil, Shashank; Patil, Sachin; Vartak, Ketan (Journal of Neonatal Surgery, 2025)
Introduction Hypospadias is a congenital anomaly commonly in males. In India, according to 2011 census, the incidence of hypospadias is around one in 150 to one in 300 males child birth. Western countries have distal hypospadias as the most common variety, whereas in Asian countries the proximal varieties are more common. The total number of documented variations exceed 200. The tubularised incised plate (TIP) urethroplasty technique has gained widespread recognition and adoption following its popularization by Snodgrass in 1994. This manuscript aims to provide a comprehensive overview of the current state of the TIP technique for the repair of coronal, distal, mid and proximal penile hypospadias. Materials and Methods This study reviewed all the TIP hypospadias repairs done from August 2016 to July 2022 in the department of urology at a tertiary hospital. All the children upto thirteen years of age with coronal, distal, mid and proximal penile hypospadias were included in the study. We collected the demographic data alongwith the type of hypospadias, outcome of the surgery and the complications. Results The mean age of patient for hypospadias in our study was 1.6 years with a range from 11 months to 13 years. The most common hypospadias type was distal penile variety (75%). Urethra-cutaneous fistula occurred in 6.25 percent cases, meatal stenosis in 3.75 percent cases and stricture urethra at the site of the original meatus proximally in 1.25 percent cases. Patient factors that positively affect the surgical outcome were early age of repair, stretched penile length of 3.8 ± 0.9 cm, urethral plate width of 9.8 ± 1.8 mm. Distal location of the meatus with deep groove of the glans without chordee were favourable factors that were statistically significant (p-value of <0.05). Conclusion The tubularised incised plate urethroplasty technique proposed by Snodgrass stands tall for distal, mid as well as proximal hypospadias, provided the age at the time of surgery, stretched penile length, width of the urethral plate, location of the meatus, deep glans groove and absent chordee were taken care and evaluated before surgery..